The effect of different desalting methods on the quality of injected brine and pickle salted frozen cod (Gadus morhua) ... - Dargentolle, Cécile; Sveinsdóttir, Hildur Inga; Arason, Sigurjón; Sveinsdóttir, Kolbrún (Zenodo, 2024)
Þessi skýrsla er lokuð / This report is closed. ...